On-site clinical mentoring as a maternal and new-born care quality improvement method: evidence from a nurse cohort study in Nepal - Sophie Goyet; Swaraj Rajbhandari; Valerie Broch Alvarez; Aida Bayou; Sirjana Khanal; Tara Nath Pokhrel (BMC, 2020)
Abstract Background We describe an on-site clinical mentoring program aimed at improving emergency obstetrical and new-born care (EmONC) in Nepal and assess its effectiveness on nurses' knowledge and skills. In Nepal, both the maternal mortality ratio (MMR, 239/100,000 live births) and the neonatal mortality rate (NMR, 21/1000 live births) were among the highest in the world in 2016, despite impressive progress over recent decades considering the challenging environment. Methods From September 2016 to April 2018, three experienced nurses conducted repeated mentoring visits in 61 comprehensive or basic EmONC centers and birthing centers located in 4 provinces of Nepal. Using updated national training manuals and teaching aids, these clinical mentors assessed and taught 12 core EmONC clinical skills to their nurse-mentees. Clinical mentors worked with management mentors whose goal was to improve the nurses' working environment. We assessed whether the cohort of nurse-mentees performed better as a group and individually performed better at the end of the program than at baseline using relevant tests (chi-square test, Wilcoxon matched-pairs signed-rank test, and Kruskal-Wallis equality-of-population rank test). Results In total, 308 nurses were assessed, including 96 (31.2%), 77 (25.0%) and 135 (43.8%) who participated in all three, two or only one mentoring session, respectively. In total, 225 (73.0%) worked as auxiliary nurse-midwives (ANMs), while 69 (22.4%) worked as nurses. One hundred and ninety five (63.3%) were trained as skilled birth attendants, of which 45 (23.1%) were nurses, 141 (72.3%) were auxiliaries and 9 (4.6%) had other positions. The proportion of ANMs and nurse-mentees who obtained a knowledge assessment score ≥ 85% increased from 57.8 to 86.1% (p <  0.001). Clinical assessment scores increased significantly for each participant, and therefore for the group. SBA-trained mentees had better knowledge of maternal and new-born care and were better able to perform the 12 core clinical skills throughout the program. Conclusions Our study suggests that on-site clinical mentoring of nurses coupled with health facility management mentoring can improve nurses' clinical competences in and performance of maternity and new-born care. Assessing evidence of impact on patient safety would be the next stage in evaluating this promising intervention.